Local deprivation and the labour market integration of new migrants to England. Issue 17 (10th December 2019) - Clark, Ken; Garratt, Lindsey; Li, Yaojun; Lymperopoulou, Kitty; Shankley, William
ABSTRACT: Using data on new migrants to England from the Quarterly Labour Force Survey, we show how a key component of migrant integration - labour market progress in terms of wages and unemployment rates – is broadly positive in the early years after arrival across a range of migrant groups and across gender. However, the precise level of labour market success achieved varies considerably across groups reflecting both the initial entry-level and labour market trajectories after migration. Migrants from Western Europe and the Old Commonwealth countries have unemployment rates (wages) which are generally lower (higher) than other groups, particularly non-white groups, while migrants from the Accession countries experience relatively low unemployment but also low wages. Groups which have better outcomes on entry also tend to experience higher rates of progress over time in England. However, the extent of multiple deprivation in the local authority where migrants reside interacts with years since migration to dampen wage trajectories for some groups and accounting for deprivation highlights the importance of internal migration for access to employment. The results emphasise structural explanations for patterns of labour market integration of new migrants to England.